Application possibilities of thermovision technique in diagnostics of aerial systems of radio transmitters - Šimko, Milan; Michalík, Ján; Chupáč, Milan (Transport, 2007)
The paper deals with possibilities of use of thermovision technique in diagnostics of aerial systems of radio transmitters. Graphically presented: heating characteristic of the junction at the transmitter power of 60% (slack and polluted junction); relationship between temperature of connection (feeder – line, capacitor frame) spacing collar and power; relationship between temperature rise amount of connection and feeder line upon power; thermogram of the junction feeder line – spacing collar, capacity frame; thermogram of the junction feeder line – spacing collar. First Published Online: 27 Oct 2010